Neonatal Citrullinemia: Comparison of Conventional MR, Diffusion-Weighted, and Diffusion Tensor Findings - Majoie, Charles B. L. M.; Mourmans, Jeroen M.; Akkerman, Erik M.; Duran, Marinus; Poll-The, Bwee Tien (American Journal of Neuroradiology, 2004)
Summary: Conventional MR, diffusion-weighted, and diffusion tensor imaging were performed in an 8-day-old girl with citrullinemia. She had severe hyperammonemia for several days. On conventional T2-weighted MR images, symmetric, confluent high signal intensity was found in the bilateral thalami, basal ganglia, cortex, and subcortical white matter. Diffusion-weighted imaging demonstrated decreased apparent diffusion coefficient in these areas, reflecting cytotoxic edema. Follow-up MR imaging at the age of 4 months revealed subcortical cysts, ulegyric changes, and atrophy, which were most prominent in the occipital lobes. Diffusion tensor imaging revealed decreased anisotropy throughout the brain, consistent with diffuse injury to the oligodendro-axonal unit. Diffusion-weighted and diffusion tensor imaging are valuable techniques for the detection of irreversible brain damage and for the characterization of hyperintense lesions on T2-weighted MR images in patients with the neonatal form of citrullinemia.